Identifying Occupational Stress among Executive officers in Governmental and Non-governmental Organizations of Nepal - Kayastha, Rabindra (Institute of Advanced Engineering and Science, 2013)
This paper is aimed at exploring the experiences of executive officers with occupations related stress. The status of occupational stress is evaluated based on the responses from employees in executive in different organizations of Nepal. Data were collected using a questionnaire survey. The results show there is a significant relationship between occuapational stress factors. The results obtained from the regression analysis showed that stress related factors (role conflict, role …) were found to be significantly related to the total stress level, whereas the stress associated with the working stress factors were insignificant. Results would showed that the different stress and the factor total stress factor was the most significant stressor of work-related stress level (p < 0.01), indicating stressors is one of the main causes of stress among EO of Nepal.DOI : http://dx.doi.org/10.11591/ijere.v2i3.2147